Life Cycle and Ovipositional Preference of Asian Papaya Fruit Fly (Bactrocera Papayae Drew & Hancock) for Guava (Psidium Guajaya, L.) - Mohd Noor, Mohd Amir Zunnasri (2011)
Asian papaya fruit fly Bactrocera papayae is one of the insects’ pest that is very destructive and causing severe damage to guava, Psidium guajava, Linn. Details on B. papayae are still lacking compared to the other species such as B. carambolae and B. cucurbitae. This study was conducted to determine the number of larval instars, the life cycle and ovipositional preference of the B. papayae on guava. Result showed that the B. papayae underwent three larval instars which can be determined by morphometric characters of the length and width of the larvae’s bodies. The body length for the first, second and third instars were 1.27 ± 0.03, 4.33 ± 0.05 and 7.84 ± 0.07 mm respectively, whilst the width for the body were 0.23 ± 0.01, 1.04 ± 0.01 and 1.85 ± 0.03 mm respectively. Moulting took one day for each larval instar. In the life cycle study, the percentage of individuals survived decreased as the stages changed from egg until adult. Findings showed that the eggs hatched after 1.16 days. Larvae underwent three instars and survived for 12.02 ± 0.13 days before entering the pupal stage. Pupae collected emerged as the adults after 7.03 ± 0.08 days. It was observed that the longevity of the adult male B. papayae was not significantly (P>0.05) different compared to the female adult. The ovipositional preference could be determined by investigating the number of larvae laid by single female per guava. Bactrocera papayae female was observed preferred to oviposit on the mature guavas in both choice and no-choice experiments. There was no significantly different between the numbers of ovipositional punctures made and larvae laid on guavas in the choice and no-choice experiments. There was a significantly different (P<0.05) in the number of larvae obtained at different maturity stages in both choice and no-choice experiments. In the choice and no-choice experiments, the numbers of larvae observed were comparatively higher in more ripened guavas than less ripened ones. This indicated that mature guavas provide more needs and nutrients required by the larvae to grow